Higher education and working life : collaborations, confrontations and challenges - Tynjälä, Päivi; Välimaa, Jussi; Boulton-Lewis, Gillian, 1940- (Advances in learning and instruction series., 2006)
This book provides a comprehensive discussion of the relationship between higher education and working life from three different perspectives: society, higher education and the world of work. The purpose of the volume is twofold: first, to critically analyse the relationship between higher education and working life, and second, to offer material that helps university teachers develop their teaching in a way that their students will be better prepared for challenges of the continuously changing world. The chapters discuss the interplay between education and work both from the societal point of.